EFFECT OFSEASONING FLAVOR RENDANGON THE QUALITY AND CONSUMER ACCEPTANCE OF SMALL SHRIMP (Acetes erythraeus) SAGO NOODLES INSTANT - Nur Irdawati; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            The purpose of this research was to determine the effect of seasoning flavor rendang on the quality and consumer acceptance of small shrimp (acetes erythraeus) sago noodles instant and analyze with organoleptic, microbiology and proximate. That was provide of flavour rendang seasoning  with4 levels: R0 (0%), R1 (5%), R2 (7%), and R3 (9%). The results of the analysis showed that small shrimpsago noodles instantwith 9%/54 gram of seasoning flavor rendang (R3) was most preferable by consumerwith 53 panelists (65.94%). The organoleptic value was significant effect on the confidence level of 95%, wherein the value of appearance 3.52 (reddish brown), flavor 3.51 (flavor rendang wasnot strong and not bitter), texture value 3.48 (a little crumbly), and aroma value 3.64 (typical of aroma rendang), meanwhile theTotal Plate Number, moisture, ash, fat, protein, carbohydrate and crude fiber was 3.6 x 103 cells/g, 8.60%, 3.53%, 0.15%, 8.15%,  79.59%, 0.22%, respectively.  Keywords:noodle, sago, seasoning flavor rendang, small shrimp